Acute exercise remodels mitochondrial membrane interactions in mouse skeletal muscle - Picard, Martin; Gentil, Benoit J.; McManus, Meagan J.; White, Kathryn; St. Louis, Kyle; Gartside, Sarah E.; Wallace, Douglas C.; Turnbull, Douglass M. (Journal of applied physiology (1985), 2013)
A unique property of mitochondria in mammalian cells is their ability to physically interact and undergo dynamic events of fusion/fission that remodel their morphology and possibly their function. In cultured cells, metabolic perturbations similar to those incurred during exercise influence mitochondrial fusion and fission processes, but it is unknown whether exercise acutely alters mitochondrial morphology and/or membrane interactions in vivo. To study this question, we subjected mice to a 3-h voluntarily exercise intervention following their normal physical activity patterns, and quantified mitochondrial morphology and membrane interactions in the soleus using a quantitative electron microscopy approach. A single exercise bout effectively decreased blood glucose ( P < 0.05) and intramyocellular lipid content ( P < 0.01), indicating increased muscle metabolic demand. The number of mitochondria spanning Z-lines and proportion of electron-dense contact sites (EDCS) between adjacent mitochondrial membranes were increased immediately after exercise among both subsarcolemmal (+116%, P < 0.05) and intermyofibrillar mitochondria (+191%, P < 0.001), indicating increased physical interactions. Mitochondrial morphology, and abundance of the mitochondrial pro-fusion proteins Mfn2 and OPA1 were unchanged. Collectively, these results support the notion that mitochondrial membrane dynamics are actively remodelled in skeletal muscle, which may be regulated by contractile activity and the metabolic state. Future studies are required to understand the implications of mitochondrial dynamics in skeletal muscle physiology during exercise and inactivity.